(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Over the twelve yearssince the production of The Satanic Verses, Salman Rushdie has been commendedas a saint on the house discourse, trashed as an impostor of Islam, andgenerally as of late, since the lifting of the fatwa in 1998, reproduced as asymbol of prevalent society. His conversion into a symbol is inquisitively wellsuited, since it is greatly because of his medication of what may be termednotorious material in his fiction. This article analyzes his short story, ’theProphet’s Hair’ as an investigation of the status of the notorious in Rushdie’scomposing: that is, his fictional medication of pictures, images or statementswhich convey conspicuously hallowed meanings. It delineates the degree to whichthe symbol’s importance is resolved by the setting in which it is set, and itscapacity to subvert and destabilize the points of confinement put upon itsimportance by such an encircling. It will fight that the political suggestionsof hybridity in Rushdie’s work are best grasped in wording of this engagementwith and recontextualization of famous material, which is not just a ’bearingover’s, in the expressions of Rushdie’s article ’imaginary Countries’, and yeta burglary, and a demonstration of willful contemptuousness.